EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN JAGUNG (Zea mays L.) DI KECAMATAN POPAYATO KABUPATEN POHUWATO - Thaib Yahya; Nurdin Nurdin; Fitriah Suryani Jamin; Rival Rahman (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2023)
Utilization of land resources requires information of the potential and limitations of land use so that the commodity that will be cultivated can achieve optimal yields. The aim of this study was to determine land suitability class of maize (Zea mays L.) of agriculture land in Popayato District, Pohuwato Regensy. This research was conducted from July 2022 to December 2022. Land suitability classes, both actual and potential, were determined based on the matching method between land characteristics of each land unit with the land suitability criteria for maize. The results showed that the actual land suitability class for maize in Popayato District was dominated by marginally suitable (S3 class) respectively at about 95.32% and not suitable (N class) about 4.68% of total area. Limiting factors consisting of class S3 includes: rainfall and humidity, soil depth, base saturation and pH, while the limiting factors in class N was soil depth. After improvement efforts were made, the potential land suitability class for maize plants became S3 class for all land units with an area of 3,587.37 ha.